KINERJA EMPAT KANTOR KECAMATAN DI KABUPATEN NGAWEN - Samodra Wibawa (Jurnal Manajemen Kepegawaian, 2011)
This article reports the result of a reasearch on the performance of four district administrations in Ngawen Residency. It is found, that the district that is the best in performance has the lowest degree of participation and accountability. Vice versa, the district that performs the worst has very low efficiency, personal capability and service quality but very high degree of participation. Are efficiency and participation a zero sum game? In accordance to the fact, the best perform district has also the worst in the factor of communication, motivation and organization climate. This means, that the best perform district is clearly less democratic. Factor that influence performance significantly is leadership, whereas factors that influence performance moderately are personnel quality, organizational structure, and organizational system and procedure. Meanwhile the quality of equipments has methodologically no evidence, that it influences performance. Key words: performance, efficiency, participation